Comparison of Indonesian and Malaysian Legal Systems in Rules, Traditions, and Community Behavior - Siti Zuliyah (Journal of Transcendental Law, 2021)
This article aims to compare the legal system in Indonesia with the legal system in Malaysia by looking at the similarities and differences between the two countries legal systems. In this paper, we use a normative juridical approach, which is to examine the laws and regulations as well as the attitudes and behavior patterns of citizens towards the law and legal system in force in a country based on secondary legal sources consisting of legislation and other related documents. The results of the discussion conclude that in general both Indonesia and Malaysia have similarities in terms of: (1) The structure of the highest judicial institution along with the judicial institutions below it as well as the implementing institutions of statutory regulations. (2) Regulations, rules and real behavior patterns in various fields of life of the citizens concerned. (3) Attitudes towards the law and the legal system of citizens are in the form of beliefs, values, awareness, ideas and hopes that make the legal process work. Meanwhile, specifically between Indonesia and Malaysia have differences due to: (1) Legal structures influenced by local or domestic and global legal traditions. (2) Legislative regulations whose formulation is influenced by local or domestic and global legal traditions. (3) The legal process runs according to the situation, conditions and problems faced by the country concerned.Keywords: Comparison of the legal system, the legal system in Indonesia, the legal system in Malaysia.